Common Bean Productivity Following Diverse Boron Applications on Soil - Flores, Rilner Alves; Silva, Talles Victor; Damin, Virginia; Marques Carvalho, Renata De Castro; Marques Pereira, Debora Regina; Souza Junior, Jonas Pereira de [UNESP] (Taylor & Francis Inc, 2018)
Aspects related to micronutrients management are still poorly studied and need to be clarified to guarantee sustainable production. In this way, the study aimed to evaluate boron (B) fertilization effects on nutrition and production of common beans. The parameters measured were relative chlorophyll index, dry mass, boron transport, utilization and absorption efficiencies, B content, and B accumulation in plant tissues. The study showed that the dry mass production was negatively affected by B application, with linear dry mass decrease following the increase of B doses. Accordingly, it was found that the common bean cultivar Esplendor presented high absorption capacity of boron, and can reach 175 mg kg(-1). However, the high absorption caused phytotoxicity and reduced dry matter production by up to 30%, reflecting the efficiency of boron use by the plant, which was reduced in up to 75%.
Keywords: Common bean; micronutrients; nutritional efficiency; plant nutrition; soil fertility